Association of pain catastrophizing longitudinally with pain severity and interference in patients with chronic pain and cancer: A CHOIR study. Issue 28 (1st October 2022) - Azizoddin, Desiree Rachel; Wilson, Jenna; Mackey, Sean; Flowers, Kelsey Mikayla; Darnall, Beth; Edwards, Robert; Schreiber, Kristin L.
Abstract : 213 Background: Understanding how psychosocial factors change during cancer and affect chronic pain outcomes may help identify potential interventional targets. This longitudinal cohort study of cancer patients investigated the relationship between changes in psychosocial factors and worsened pain severity and interference over time using the Collaborative Health Outcomes Information Registry (CHOIR) dataset. Methods: Data from patients with cancer and chronic pain (n = 316) treated at a tertiary pain clinic were prospectively collected. At their initial visit (baseline; Time 1), patients provided demographic and clinical information, and completed validated psychosocial and pain assessments. Psychosocial and pain assessments were repeated at Time 2, on average 4.9 months later. Change scores (Time 2-Time 1) were computed for psychosocial and pain variables. Multivariable hierarchical linear regressions assessed the associations between changes in psychosocial factors with changes in pain outcomes over time. Results: Participants had an average age of 59, were 61% female, and 69% White. Overall, a decrease in pain severity ( p ≤.001), but not pain interference, was observed among the group from T1 to T2. Increased pain catastrophizing was significantly associated with increased pain severity over time (b= 0.24, p ≤.001). Similarly, increased pain catastrophizing (b= 0.21, p ≤.001) and increased depression (b= 0.20, p ≤.003) were significantly associated with increased pain interference over time. Demographic and clinical characteristics were not significantly related to changes in pain outcomes. Conclusions: Increased catastrophizing was uniquely associated with increased chronic pain severity and interference. Future interventional studies investigating the utility of nonpharmacological approaches that address psychological processes, like catastrophizing, for patients with cancer and chronic pain are needed.